Secondary battery and electric device
Patent Information
- Application Number
- CN202380044953.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-01-10
AI Technical Summary
Existing secondary batteries have a large volume expansion rate of silicon-based materials during the charge and discharge process, resulting in poor cycle performance, making it difficult to achieve both high energy density and excellent cycle performance.
A silicon-carbon composite material with a three-dimensional network cross-linked pore structure is used as the negative electrode material, and a component containing a cyclic functional group containing a sulfate ester group or a sulfonate ester group is added to the electrolyte to generate a sulfate-containing oxide by improving the interfacial film formation. Interface components enhance the chemical and thermal stability of the electrolyte/electrode interface, thereby improving the cycle performance of the battery.
It significantly improves the battery's cycle capacity retention rate and storage performance under high temperature conditions, reduces the internal resistance of the battery, and enhances the structural stability and energy density of the negative active material.
Smart Images

Figure CN119301792A_ABST
Abstract
Description
Secondary batteries and electrical devices Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a secondary battery and an electrical device. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] Electrode active materials with high gram capacity often have poor cycle performance. How to improve the battery energy density while taking into account excellent cycle performance through the mutual coordination of various battery components is a technical problem that needs to be solved urgently in this field.
[0004] Summary of the Invention
[0005] This application is made in view of the above-mentioned problems, and its purpose is to provide a secondary battery. By matching the electrolyte and the negative electrode material, the interface stability is improved, and the cycle capacity retention rate and storage capacity retention rate of the battery under high temperature conditions are improved.
[0006] The first aspect of the present application provides a secondary battery, characterized in that it includes a negative electrode plate and an electrolyte; the negative electrode plate includes a silicon-carbon composite material with a three-dimensional network cross-linked pore structure; the electrolyte contains a first component, and the first component contains a cyclic functional group containing a sulfate group or a sulfonate group.
[0007] The silicon-carbon composite material with a three-dimensional network cross-linked pore structure has a stable porous skeleton and good mechanical strength. It can effectively reduce the volume change of silicon before and after charge and discharge while loading a high silicon content. At the same time, the first component in the electrolyte can participate in interfacial film formation, generating a sulfate-containing interfacial component, constructing a stable electrolyte / electrode interface, and improving the chemical and thermal stability of the interface, thereby enhancing the battery's cycling performance and effectively improving the battery's storage performance under high temperature conditions.
[0008] In any embodiment, the first component comprises at least one compound of Formula I, Formula II, or Formula III, H—L1 Formula I
[0009] Among them, L1-L6 each independently includes m is any integer from 0 to 8. When m is 0, L2 and L3 are connected by a single bond;
[0010] R1, R2, and R3 are independently H, F, fluorine-substituted or unsubstituted C1-C10 Saturated or unsaturated hydrocarbon group, C6~C 60 At least one of aryl, carbonyl, carboxyl, ester, cyano, silane, and ether groups; M contains at least one of O and C; and n is any integer from 0 to 3.
[0011] In any embodiment, the first component includes one or more of Compound A-1 to Compound A-10:
[0012] The above-mentioned compounds A-1 to A-10 can participate in interfacial film formation, generate sulfate-containing interfacial components, improve the chemical stability and thermal stability of the interface, construct a stable electrolyte / electrode interface, thereby improving the cycle performance of the battery and effectively improving the storage performance of the battery under high temperature conditions.
[0013] In any embodiment, the specific surface area of the silicon-carbon composite material is SSA m 2 / g,
[0014] Based on the total mass of the electrolyte, the mass proportion of the first component is EL g / g,
[0015] EL: SSA is 0.0001~0.03, and can be optionally 0.0004~0.01.
[0016] When the ratio EL:SSA between the mass proportion of the first component in the electrolyte and the specific surface area SSA of the silicon-carbon composite material meets the above range, the first component can effectively enter the pore structure of the silicon-carbon composite material, fully contact with the silicon-carbon composite material, increase the migration rate of ions at the electrode / electrolyte interface, reduce the internal resistance of the battery, and improve the cycle capacity retention rate of the battery.
[0017] In any embodiment, based on the total mass of the electrolyte, the mass proportion of the first component is EL g / g, and the mass percentage of silicon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material in the peripheral region of the silicon-carbon composite material is B1, wherein the peripheral region of the silicon-carbon composite material is an area extending from the outer surface of the silicon-carbon composite material to the interior of the silicon-carbon composite material within a distance of r / 2, where r represents the short diameter of the silicon-carbon composite material.
[0018] EL: B1 is 0.001~0.1, and can be optionally 0.005~0.06.
[0019] When the ratio between the mass percentage of the first component in the electrolyte and the mass percentage B1 of the silicon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material meets the above range, it is beneficial to alleviate the volume expansion of silicon during the charging and discharging process, improve the structural stability of the silicon-carbon composite material, and thus improve the cycle stability of the battery.
[0020] In any embodiment, the total pore volume of the pores with a pore diameter greater than 100 nm in the silicon-carbon composite material is V1 cm 3 / g, and the ratio EL:V1 between the mass proportion EL of the first component in the electrolyte and the total pore volume V1 of pores with a pore diameter greater than 100 nm in the silicon-carbon composite material is 1 to 30, and can be optionally 2 to 15.
[0021] When the ratio EL:V1 between the mass proportion EL of the first component in the electrolyte and the total pore volume V1 of pores with a pore diameter greater than 100 nm in the silicon-carbon composite material meets the above range, the first component can be smoothly embedded in the pore structure of the silicon-carbon composite material, forming mutual cooperation with it to further improve the migration rate of ions in the electrode active material, reduce the internal resistance of the battery, and improve the cycle capacity retention rate of the battery.
[0022] In any embodiment, in the peripheral area of the silicon-carbon composite material, the mass percentage A1 of the carbon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material and the mass percentage B1 of the silicon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material satisfy 0.8≤B1 / A1≤2.5, optionally, 1≤B1 / A1≤1.5.
[0023] In the peripheral region of the silicon-carbon composite material, when the mass percentage A1 of the carbon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material and the mass percentage B1 of the silicon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material meet the above-mentioned range, the mass of silicon in the pore structure of the silicon-carbon composite material is relatively high, which can significantly increase the capacity of the negative electrode active material, and the voltage for metal ion embedding is low, which is conducive to the embedding of metal ions, thereby improving the rate performance of the secondary battery. At the same time, the three-dimensional network cross-linked pore structure can inhibit the volume expansion of silicon during the cycle, improve the structural stability of the negative electrode active material, and thus improve the cycle performance of the battery.
[0024] In any embodiment, the mass percentage A of the carbon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material has a decreasing trend along the direction from the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material, and the mass percentage B of the silicon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material has an increasing trend along the direction from the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material.
[0025] Since the silicon-carbon composite material may have an irregular shape, the geometric center of the silicon-carbon composite material can be equated with the geometric center of a rectangular parallelepiped tangent to it. From the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material, the mass percentage of carbon (A) gradually decreases, while the mass percentage of silicon (B) gradually increases. This gradually increases the silicon content in the pore structure of the silicon-carbon composite material. A relatively high silicon content can significantly improve the capacity of the negative electrode active material.
[0026] In any embodiment, the specific surface area SSA of the silicon-carbon composite material satisfies: 2m 2 / g≤SSA≤10m 2 / g; optionally, 3m 2 / g≤SSA≤7m 2 / g.
[0027] When the specific surface area SSA of the silicon-carbon composite material meets the above range, the specific surface area of the silicon-carbon composite material is large, the kinetic properties of the material are good, and it is beneficial to improve the first coulombic efficiency of the battery.
[0028] In any embodiment, the silicon-carbon composite material includes carbon matrix particles and silicon nanoparticles, the carbon matrix particles include a three-dimensional network cross-linked pore structure; at least a portion of the silicon nanoparticles is disposed in the three-dimensional network cross-linked pore structure.
[0029] When the silicon-carbon composite material of the present application is applied to a secondary battery, the cycle performance and energy density of the secondary battery can be improved.
[0030] In any embodiment, the silicon nanoparticles include one or more of silicon oxide compounds, pre-lithium silicon oxide compounds, amorphous silicon, crystalline silicon, and silicon-carbon composites, and may be amorphous silicon.
[0031] In any embodiment, the carbon matrix includes one or more of graphite, soft carbon, and hard carbon.
[0032] In any embodiment, the mass ratio of the silicon nanoparticles in the silicon-carbon composite material is greater than or equal to 40%, and can be optionally 40-60%.
[0033] The negative electrode material used in the secondary battery of the present application achieves a high loading amount of silicon nanoparticles in the negative electrode material by adopting a carbon-based material having a three-dimensional network cross-linked pore structure, so that the silicon-carbon composite material has a high capacity and can further improve the energy density of the battery.
[0034] In any embodiment, the powder compaction density of the silicon-carbon composite material after one powder compaction test under a force of 20,000 N is P11 g / cm 3The compaction density of the silicon-carbon composite material after 20 powder compaction tests under a force of 20000N is P21g / cm 3 The ratio satisfies: 1.00<P21 / P11≤1.20, optionally, 1.02≤P21 / P11≤1.10.
[0035] When the ratio of P21 / P11 satisfies the above range, the silicon-carbon composite material has a higher gram capacity and better compressive resistance, thereby improving the structural stability of the negative electrode film layer, so that the secondary battery containing this material has a higher energy density while also having better cycle performance.
[0036] In any embodiment, the powder compaction density of the silicon-carbon composite material after one powder compaction test under a force of 20,000 N is P11 g / cm 3 Satisfies: 1.10≤P11≤1.40, optionally, 1.12≤P11≤1.35.
[0037] The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3 When the above range is met, the negative electrode film layer has a higher compaction density, so that the secondary battery has a higher energy density.
[0038] In any embodiment, the secondary battery includes at least one of a lithium ion battery, a sodium ion battery, a magnesium ion battery, and a potassium ion battery.
[0039] A second aspect of the present application provides an electrical device comprising the secondary battery of the first aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0041] FIG2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG1 ;
[0042] FIG3 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0043] Description of reference numerals: 1 secondary battery; 11 housing; 12 electrode assembly; 13 cover plate. DETAILED DESCRIPTION
[0044] Below, the embodiments of the binder, preparation method, electrode, battery, and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0045] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0046] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0047] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0048] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0049] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0050] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0051] As the application of secondary batteries expands, requirements for secondary battery performance, such as energy density, are gradually increasing. Silicon-based materials have high specific capacity, making them suitable negative electrode materials for high-energy-density batteries. However, silicon-based materials have a large volume expansion rate during charge and discharge, resulting in poor battery cycle performance.
[0052] Based on this, the present application provides a secondary battery, which includes: a negative electrode plate and an electrolyte, the negative electrode plate includes a silicon-carbon composite material with a three-dimensional network cross-linked pore structure; the electrolyte contains a first component, and the first component contains a cyclic functional group containing a sulfate group or a sulfonate group.
[0053] In this article, the three-dimensional network cross-linked pore structure generally refers to a structure in which two or more pores are interconnected or interlaced and share pore volume in a silicon-carbon composite material, especially in a pore structure formed by carbon matrix particles.
[0054] The pore structure of the silicon-carbon composite material can be tested using equipment and methods known in the art. For example, it can be tested by using a scanning electron microscope (such as ZEISS Sigma 300). As an example, the following steps can be followed: first, the negative electrode sheet containing the silicon-carbon composite material is cut into a sample to be tested of a certain size (for example, 6 mm × 6 mm), and the sample to be tested is clamped with two conductive and heat-conductive thin sheets (such as copper foil), and the sample to be tested and the thin sheet are glued and fixed with glue (such as double-sided tape), and a flat iron block of a certain mass (such as about 400 g) is used to press for a certain time (such as 1 hour) to make the gap between the sample to be tested and the copper foil as small as possible, and then the edges are trimmed with scissors and glued to a sample table with conductive glue, and the sample is slightly protruding from the edge of the sample table. Then, place the sample stage into the sample holder and lock it securely. Turn on the power of the argon ion cross-section polisher (e.g., IB-19500CP) and evacuate the sample to a vacuum (e.g., 10 Pa to 4 Pa). Set the argon flow rate (e.g., 0.15 MPa), voltage (e.g., 8 kV), and polishing time (e.g., 2 hours). Adjust the sample stage to the rocking mode and start polishing. After polishing, use a scanning electron microscope (e.g., ZEISS Sigma 300) to obtain an ion polished cross-section morphology (CP) image of the sample to be tested.
[0055] The silicon-carbon composite material with a three-dimensional network cross-linked pore structure has a stable porous skeleton and good mechanical strength. It can effectively reduce the volume change of silicon before and after charge and discharge while loading a high silicon content. At the same time, the first component in the electrolyte can participate in interfacial film formation, generating a sulfate-containing interfacial component, constructing a stable electrolyte / electrode interface, and improving the chemical and thermal stability of the interface, thereby enhancing the battery's cycling performance and effectively improving the battery's storage performance under high temperature conditions.
[0056] In some embodiments, the first component comprises a compound of Formula I, Formula II, or Formula III, H—L1 Formula I
[0057] Among them, L1-L6 each independently includes m is any integer from 0 to 8. When m is 0, L2 and L3 are connected by a single bond;
[0058] R1, R2, and R3 are independently H, F, fluorine-substituted or unsubstituted C1-C 10 Saturated or unsaturated hydrocarbon group, C6~C 60 At least one of aryl, carbonyl, carboxyl, ester, cyano, silane, and ether groups; M contains at least one of O and C; and n is any integer from 0 to 3.
[0059] In this article, the terms "C1~C 10"Saturated or unsaturated hydrocarbon group" refers to a saturated or unsaturated hydrocarbon group having 1 to 10 carbon atoms. 10 Non-limiting examples of saturated or unsaturated hydrocarbon groups may include methyl (CH3-), ethyl (C2H5-), isopropyl ((CH3)2CH-), vinyl (CH2=CH-), propynyl (HC≡CCH2-), and methylene (-CH2-).
[0060] In this article, the term "C6~C 60 "Aryl" refers to a monovalent group of a carbocyclic aromatic system having 6 to 60 carbon atoms.
[0061] As used herein, "carbonyl" refers to
[0062] In this context, "carboxyl" refers to
[0063] In this context, "ester group" refers to Wherein, R is a C1-C3 hydrocarbon group.
[0064] As used herein, "cyano" refers to -C≡N.
[0065] As used herein, the term "silyl" refers to a -Si(R1)(R2)(R3) group, wherein R1, R2, and R3 are each independently selected from hydrogen, a substituted or unsubstituted C1-C3 alkyl group. By way of example, silyl groups include, but are not limited to, -SiH3 and -Si(CH3)3.
[0066] As used herein, "ether group" refers to -RO-R'-, wherein R and R' are C1-C3 hydrocarbon groups.
[0067] In some embodiments, the specific surface area of the silicon-carbon composite material is SSA m 2 / g, based on the total mass of the electrolyte, the mass proportion of the first component is EL g / g, and EL:SSA is 0.0001-0.03, and can be optionally 0.0004-0.01.
[0068] In some embodiments, the specific surface area of the silicon-carbon composite material is SSA m 2 / g, based on the total mass of the electrolyte, the mass proportion of the first component is EL g / g, and EL:SSA can be selected from 0.0001, 0.0002, 0.0003, 0.0004, 0.0005, 0.0006, 0.0007, 0.0008, 0.0009, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.015, 0.02, 0.025 or 0.03.
[0069] In this article, specific surface area SSA is a well-known meaning in the art, usually the surface area is expressed in m 2 The unit of % is expressed in g and can be measured using methods and instruments known in the art. For example, it can be measured using an inert gas (e.g., nitrogen) adsorption specific surface area analysis method according to GB / T 19587-2017 and calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis can be performed using a Tri-Star 3020 specific surface area pore size analyzer from Micromeritics, USA.
[0070] When the ratio EL:SSA between the mass proportion of the first component in the electrolyte and the specific surface area SSA of the silicon-carbon composite material meets the above range, the first component can effectively enter the pore structure of the silicon-carbon composite material, fully contact with the silicon-carbon composite material, increase the migration rate of ions at the electrode / electrolyte interface, reduce the internal resistance of the battery, and improve the cycle capacity retention rate of the battery.
[0071] In some embodiments, the mass percentage of the first component in the electrolyte is EL g / g, and the mass percentage of silicon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material is B1, wherein the peripheral area of the silicon-carbon composite material is an area extending from the outer surface of the silicon-carbon composite material to the interior of the silicon-carbon composite material within a distance of r / 2, r represents the short diameter of the silicon-carbon composite material, EL:B1 is 0.001~0.1, and can be optionally 0.005~0.06.
[0072] The three-axis diameter characterization method can be used to characterize the particle size of the silicon-carbon composite material. The specific characterization method is as follows: the long diameter l and the short diameter r are measured on the plane projection of the silicon-carbon composite material, and the thickness h of the silicon-carbon composite material is measured in the direction perpendicular to the projection plane; it can also be understood as placing the silicon-carbon composite material in a rectangular parallelepiped tangent to it, with the long side of the rectangular parallelepiped being l, the short side being r, and the thickness being h, to reflect the actual size of the silicon-carbon composite material.
[0073] The silicon content can be determined by inductively coupled plasma (ICP) emission spectroscopy test, as follows: a silicon-carbon composite material is taken as a sample, the sample is digested with aqua regia and hydrofluoric acid HF, and the solution digested for 15 minutes and the completely digested solution are taken for ICP testing. The silicon content in the solution digested for 45 minutes is the silicon content in the "peripheral area of the silicon-carbon composite material."
[0074] In some embodiments, the ratio EL:B1 between the mass percentage of the first component in the electrolyte and the mass percentage B1 of the silicon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material can be selected to be 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1.
[0075] Compared to the silicon within the silicon-carbon composite, the silicon in the outer region of the composite is less easily constrained by the carbon skeleton and expands more significantly. When the ratio of the mass percentage of the first component in the electrolyte to the mass percentage (B1) of the silicon in the composite relative to the total mass of the composite falls within the aforementioned range, it helps mitigate the volume expansion of silicon during charge and discharge, improves the structural stability of the composite, and thus enhances the cycling stability of the battery.
[0076] In some embodiments, the total pore volume of pores with a pore diameter greater than 100 nm in the silicon-carbon composite material is V1 cm 3 / g, the ratio EL:V1 between the mass proportion EL of the first component in the electrolyte and the total pore volume V1 of pores with a pore diameter greater than 100 nm in the silicon-carbon composite material is 1 to 30, and preferably 2 to 15.
[0077] The pore volume test method for different pore sizes can refer to GB / T 19587-2004, using the mesopore pore size distribution test BJH (Barret Joyner Halenda), using the gas adsorption and desorption method under the micro-mesopore model and selecting the adsorption branch data to measure and calculate the total pore volume V1 of pores with a pore size greater than 100 nm.
[0078] In some embodiments, the ratio EL:V1 between the mass proportion EL of the first component in the electrolyte and the total pore volume V1 of pores with a pore diameter greater than 100 nm in the silicon-carbon composite material can be selected as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30.
[0079] The first component easily enters the negative electrode active material through the macropores. When the ratio EL:V1 of the mass proportion of the first component in the electrolyte to the total pore volume V1 of pores with a pore diameter greater than 100 nm in the silicon-carbon composite material meets the above range, the first component easily enters the pore structure of the silicon-carbon composite material, forming a mutual cooperation with it to further increase the migration rate of ions in the electrode active material, reduce the internal resistance of the battery, and improve the cycle capacity retention rate of the battery.
[0080] In some embodiments, in the peripheral area of the silicon-carbon composite material, the mass percentage A1 of the carbon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material and the mass percentage B1 of the silicon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material satisfy 0.8≤B1 / A1≤2.5, optionally, 1≤B1 / A1≤1.5.
[0081] The carbon content can be analyzed by infrared absorption carbon-sulfur content analysis according to the GB / T20123-2006 test standard, specifically as follows: take the silicon-carbon composite material as a sample, and the carbon content at the time of testing for 20 minutes is the carbon content of the "peripheral area of the silicon-carbon composite material". In the peripheral area of the silicon-carbon composite material, when the mass percentage A1 of the carbon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material and the mass percentage B1 of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material meet the above ranges, the mass of silicon in the pore structure of the silicon-carbon composite material is relatively high, which can significantly improve the capacity of the negative electrode active material, and the voltage for metal ion embedding is low, which is conducive to the embedding of metal ions, thereby improving the cycle performance of the secondary battery. At the same time, the three-dimensional network cross-linked pore structure can inhibit the volume expansion of silicon during the cycle, improve the structural stability of the negative electrode active material, and thus improve the cycle performance of the battery.
[0082] In some embodiments, the mass percentage A of the carbon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material has a decreasing trend along the direction from the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material, and the mass percentage B of the silicon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material has an increasing trend along the direction from the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material.
[0083] Since silicon-carbon composite materials may be irregularly shaped, the geometric center of the silicon-carbon composite material can be equated with the geometric center of a rectangular parallelepiped tangent to it. From the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material, the mass percentage of carbon (A) gradually decreases, while the mass percentage of silicon (B) gradually increases. The silicon content in the pore structure of the silicon-carbon composite material gradually increases. This relatively high silicon content can significantly increase the capacity of the negative electrode active material. Furthermore, the increasing silicon content from the outer surface toward the center makes the carbon material's inhibitory effect on silicon expansion increasingly significant, further improving the battery's cycling performance.
[0084] In some embodiments, the specific surface area SSA of the silicon-carbon composite material satisfies: 2m 2 / g≤SSA≤10m 2 / g; optionally, 3m 2 / g≤SSA≤7m 2 / g.
[0085] In some embodiments, the specific surface area SSA of the silicon-carbon composite material can be selected to be 2 m 2 / g、3m 2 / g、4m 2 / g、5m 2 / g、6m 2 / g、7m 2 / g、8m 2 / g、9m 2 / g or 10m 2 / g, or a range consisting of any two of the above values.
[0086] When the specific surface area SSA of the silicon-carbon composite material meets the above range, the specific surface area of the silicon-carbon composite material is large, the kinetic properties of the material are good, and it is beneficial to improve the first coulombic efficiency of the battery.
[0087] In some embodiments, the silicon-carbon composite material includes: carbon matrix particles and silicon nanoparticles, the carbon matrix particles include a three-dimensional network cross-linked pore structure, and at least a portion of the silicon nanoparticles is disposed in the three-dimensional network cross-linked pore structure.
[0088] The carbon matrix particles of the present application have a stable porous skeleton structure, a strong supporting capacity, a high stress capacity, and excellent mechanical properties and electrical conductivity; the carbon matrix particles include a three-dimensional network cross-linked pore structure, which provides more space for embedding silicon-based nanoparticles, can be used for large-scale silicon storage, and effectively increase the silicon loading capacity in the silicon-carbon composite material. After the carbon matrix particles are compounded with the silicon-based nanoparticles, the electrical conductivity of the silicon-carbon composite material can be improved, while the volume effect of silicon in the process of lithium insertion and extraction can be alleviated, and the stress changes of the silicon-based nanoparticles can be fully withstood, thereby ensuring the structural stability of the silicon-carbon composite material and improving the cycle stability and lithium storage capacity of the silicon-carbon composite material. Therefore, when the silicon-carbon composite material is applied to a secondary battery, the cycle performance and energy density of the secondary battery can be improved.
[0089] In some embodiments, the silicon nanoparticles include one or more of silicon oxides, pre-lithium silicon oxides, amorphous silicon, crystalline silicon, and silicon-carbon composites, and may be amorphous silicon.
[0090] In some embodiments, the carbon matrix includes one or more of graphite, soft carbon, and hard carbon.
[0091] In some embodiments, the mass ratio of silicon nanoparticles in the silicon-carbon composite material is greater than or equal to 40%, and can be optionally 40-60%.
[0092] In some embodiments, the mass ratio of silicon nanoparticles in the silicon-carbon composite material may be 40%, 45%, 50%, 55% or 60%.
[0093] The quality of silicon nanoparticles in silicon-carbon composite materials can be tested using methods and equipment known in the art, for example, it can be measured with reference to EPA 6010D-2014 standard; specifically, ICP-OES (elemental analysis-inductively coupled plasma optical emission spectrometry) testing can be used, in which the solid to be tested is first dissolved into a liquid with a strong acid, and then the liquid is introduced into an ICP light source by atomization. The gaseous atoms to be tested are further ionized and excited in a strong magnetic field, and then restored to the ground state from the excited state; in the above process, energy is released and recorded as different characteristic spectral lines for quantitative analysis of trace elements.
[0094] The negative electrode material used in the secondary battery of the present application achieves a high loading amount of silicon nanoparticles in the negative electrode material by adopting a carbon-based material having a three-dimensional network cross-linked pore structure, so that the silicon-carbon composite material has a high capacity and can further improve the energy density of the battery.
[0095] In some embodiments, the powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3The compaction density of the silicon-carbon composite material after 20 times of powder compaction under a force of 20,000 N is P21 g / cm 3 The ratio satisfies: 1.00<P21 / P11≤1.20, optionally, 1.02≤P21 / P11≤1.10.
[0096] When the ratio of P21 / P11 satisfies the above range, the silicon-carbon composite material has a higher gram capacity and better compressive resistance, thereby improving the structural stability of the negative electrode film layer, so that the secondary battery containing this material has a higher energy density while also having better cycle performance.
[0097] In some embodiments, the powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3 Satisfies: 1.10≤P11≤1.40, optionally, 1.12≤P11≤1.35.
[0098] The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20,000 N is P11 g / cm 3 When the above range is met, the negative electrode film layer has a higher compaction density, so that the secondary battery has a higher energy density.
[0099] In some embodiments, the compound represented by Formula I includes one or more of Compound A-1 to Compound A-10:
[0100] The above-mentioned compounds A-1 to A-10 can all participate in interfacial film formation, generate sulfate-containing interfacial components, improve the chemical stability and thermal stability of the interface, construct a stable electrolyte / electrode interface, thereby improving the cycle performance of the battery and effectively improving the storage performance of the battery under high temperature conditions.
[0101] In some embodiments, a secondary battery includes a negative electrode sheet, wherein the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0102] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0103] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0104] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0105] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0106] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0107] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0108] In some embodiments, a secondary battery includes a positive electrode sheet, which includes a positive electrode collector and a positive electrode film layer disposed on at least one surface of the positive electrode collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0109] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0110] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0111] In some embodiments, the positive electrode active material may adopt the positive electrode active material for batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0112] In some embodiments, the positive electrode active material is a nickel-rich material, and the molar ratio of nickel in the transition metal of the positive electrode active material is higher than 85%.
[0113] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0114] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0115] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0116] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0117] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0118] In some embodiments, the secondary battery includes at least one of a lithium ion battery, a sodium ion battery, a magnesium ion battery, and a potassium ion battery.
[0119] In one embodiment of the present application, an electric device is provided, comprising the secondary battery of any embodiment.
[0120] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 1 with a square structure as an example.
[0121] In some embodiments, referring to Figure 2, the outer packaging may include a shell 11 and a cover plate 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the secondary battery 1 can be one or more, and those skilled in the art can select according to specific actual needs.
[0122] An electrical device includes the secondary battery provided in this application. The secondary battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. Electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.
[0123] Figure 3 shows an example of an electric device. This device can be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0124] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0125] Example
[0126] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0127] Primary and secondary batteries
[0128] Example 1
[0129] (1) Preparation of silicon-carbon composite materials
[0130] Providing a gas containing a silicon precursor to carbon matrix particles having a three-dimensional network cross-linked pore structure;
[0131] Silicon nanoparticles attached to the carbon matrix particles are generated from the silicon precursor through chemical vapor deposition to obtain a silicon-carbon composite material.
[0132] (2) Preparation of negative electrode sheet
[0133] The negative electrode active material (silicon-carbon composite material), conductive carbon black, thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber latex (SBR) are fully stirred and mixed in an appropriate amount of deionized water at a weight ratio of 96.5:1.0:1.0:1.5 to form a uniform negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying and other processes, a negative electrode sheet is obtained.
[0134] (3) Preparation of positive electrode sheet
[0135] Aluminum foil with a thickness of 8 μm was used as the positive electrode current collector. 0.8 Co 0.1 Mn 0.1 O2(NCM 811 ), the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) are dissolved in the solvent N-methylpyrrolidone (NMP) in a weight ratio of 93:2:5, and the mixture is fully stirred to obtain a positive electrode slurry; the positive electrode slurry is then evenly coated on the positive electrode collector, and then dried, cold pressed, and cut to obtain a positive electrode sheet.
[0136] (4) Preparation of electrolyte
[0137] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to prepare an organic solvent. Thoroughly dried lithium salt LiPF6 was then dissolved in the mixed organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L. 1 wt% of Compound A-1 was then added to the electrolyte solution and mixed thoroughly.
[0138] (5) Isolation membrane
[0139] Polypropylene film is used as the isolation film.
[0140] (6) Preparation of batteries
[0141] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator positioned between the positive and negative electrode sheets to provide isolation. The cells are then wound to obtain a bare cell. The tabs are welded to the bare cell and placed in an aluminum shell. The cells are then baked at 80°C to remove moisture. The electrolyte is then injected and sealed to obtain an uncharged battery. The uncharged battery then undergoes a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the lithium-ion battery product of Example 1.
[0142] Example 2-10
[0143] The preparation method of the battery of Example 2-10 is similar to that of Example 1, but the types of additives are adjusted. The specific parameters are shown in Table 1.
[0144] Examples 11-14
[0145] The preparation methods of the batteries of Examples 11-14 are similar to those of Example 1, but the contents of the electrolyte additives are adjusted so that EL:SSA, EL:B1, and EL:V1 vary. The specific parameters are shown in Table 1.
[0146] Examples 15-18
[0147] The preparation methods of the batteries of Examples 15-18 are similar to those of Example 1, but the deposition positions of the silicon particles of the silicon-carbon composite material are adjusted to adjust the values of EL:B1. The specific parameters are shown in Table 1.
[0148] Examples 19-22
[0149] The preparation methods of the batteries of Examples 19-22 are similar to those of Example 1, but the pore size distribution of the silicon-carbon composite material is adjusted to adjust the EL:V1 value. The specific parameters are shown in Table 1.
[0150] Comparative Example 1
[0151] The preparation method of the battery of Comparative Example 1 is similar to that of Example 1, but the first component is not added to the electrolyte.
[0152] Comparative Example 2
[0153] The preparation method of the battery of Comparative Example 2 is similar to that of Example 1, but the pore structure of the carbon matrix particles of Comparative Example 2 is a honeycomb pore structure.
[0154] Comparative Example 3
[0155] The preparation method of the battery of Comparative Example 3 is similar to that of Example 2, but the pore structure of the carbon matrix particles of Comparative Example 3 is a honeycomb pore structure.
[0156] Comparative Example 4
[0157] The preparation method of the battery of Comparative Example 4 is similar to that of Example 3, but the pore structure of the carbon matrix particles of Comparative Example 4 is a honeycomb pore structure.
[0158] 2. Test Method
[0159] 1. Silicon-carbon composite materials
[0160] 1) Structural characterization of silicon-carbon composites
[0161] The pore structure of the silicon-carbon composite material can be tested using equipment and methods known in the art. For example, it can be tested by using a scanning electron microscope (such as ZEISS Sigma 300). As an example, the following steps can be followed: first, the negative electrode sheet containing the silicon-carbon composite material is cut into a sample to be tested of a certain size (for example, 6 mm × 6 mm), and the sample to be tested is clamped with two conductive and heat-conductive thin sheets (such as copper foil), and the sample to be tested and the thin sheet are glued and fixed with glue (such as double-sided tape), and a flat iron block of a certain mass (such as about 400 g) is used to press for a certain time (such as 1 hour) to make the gap between the sample to be tested and the copper foil as small as possible, and then the edges are trimmed with scissors and glued to a sample table with conductive glue, and the sample is slightly protruding from the edge of the sample table. Then, place the sample stage into the sample holder and lock it in place. Turn on the argon ion cross-section polisher (e.g., IB-19500CP) and evacuate the sample to a vacuum (e.g., 10 Pa to 4 Pa). Set the argon flow rate (e.g., 0.15 MPa), voltage (e.g., 8 kV), and polishing time (e.g., 2 hours). Adjust the sample stage to rocking mode and begin polishing. After polishing, use a scanning electron microscope (e.g., ZEISS Sigma 300) to obtain an ion-polished cross-section morphology (CP) image of the sample to be tested.
[0162] 2) Specific surface area SSA of silicon-carbon composite material
[0163] The specific surface area was tested using the gas adsorption method in accordance with the GB / T19587-2017 test standard, as follows: after disassembling the battery, scrape the negative electrode powder and obtain a silicon-carbon composite material powder sample after high-temperature ablation. The sample tube was immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures was measured at a relative pressure of 0.05-0.30. The monolayer adsorption amount of the sample was obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area of the negative electrode active material.
[0164] The BET calculation formula is as follows:
[0165] Where n a —amount of adsorbed gas, in mol / g; p / p0 —relative pressure; nm —monolayer adsorption capacity; C represents a correction parameter, which is used to limit the number of adsorption layers on the adsorbent surface.
[0166] 3) Pore size of silicon-carbon composite material
[0167] The pore size is tested by gas adsorption method according to the test standards GB / T19587-2017 & GB / T21650.2-2008. The specific test method is as follows: a silicon-carbon composite material is taken as a sample, and the sample tube is immersed in liquid nitrogen at -196°C. Nitrogen is adsorbed on the material to be tested at a relative pressure of 0-1. The pore size distribution of the porous material is characterized based on the relationship between the volume of each pore size and the corresponding partial pressure.
[0168] 4) Powder compaction density
[0169] Refer to GB / T 24533-2009 and use an electronic pressure testing machine (such as UTM7305) to test: place a powder sample of a certain mass G on a special compaction mold (bottom area S), set different pressures (20000N or 50000N can be used in this application), maintain the pressure for 20 seconds, release the pressure, wait for 10 seconds, read the thickness H of the powder after compaction under the pressure on the equipment, and calculate the compaction density under the pressure. The compaction density of the material under the pressure = G / (H*S).
[0170] 5) Characterization of silicon and carbon element distribution in silicon-carbon composites
[0171] The elemental distribution of the particle cross section was tested by energy dispersive ion polishing cross section element analysis according to the GB-T17359-2012 test standard.
[0172] 6) Test of silicon content in silicon-carbon composite materials
[0173] The silicon content was determined by emission spectroscopy (Inductively coupled plasma, ICP), specifically as follows: a silicon-carbon composite material was taken as a sample, and the sample was digested with aqua regia and hydrofluoric acid HF. The solution digested for 15 minutes and the solution completely digested were taken for ICP testing. The silicon content in the solution digested for 45 minutes was the silicon content in the "peripheral area of the silicon-carbon composite material", and the difference between the silicon content in the solution completely digested and that in the solution digested for 1 hour was the silicon content in the "central area of the silicon-carbon composite material".
[0174] 7) Carbon content test in silicon-carbon composite materials
[0175] The carbon-sulfur content analysis by infrared absorption method is tested according to the GB / T20123-2006 test standard, as follows: the silicon-carbon composite material is taken as a sample, and the carbon content at 20 minutes of testing is the carbon content of the "peripheral area of the silicon-carbon composite material", and the difference between the carbon content at 20 minutes of testing and the end of the test is the carbon content of the "peripheral area of the silicon-carbon composite material".
[0176] 8) Short diameter r test of silicon-carbon composite materials
[0177] The short diameter r is measured according to the three-axis characterization method, specifically as follows: the short diameter r is measured on a plane projection diagram of the silicon-carbon composite material.
[0178] 2. Battery performance
[0179] 1) High temperature cycle capacity retention rate
[0180] At 45°C, the secondary batteries prepared in each example and comparative example were charged at a constant current rate of 0.5C to a charge cutoff voltage of 4.25V. They were then charged at a constant voltage rate to a current of ≤0.05C, allowed to rest for 5 minutes, and then discharged at a constant current rate of 0.33C to a discharge cutoff voltage of 2V, allowed to rest for 5 minutes. This constituted one charge-discharge cycle. The batteries were subjected to cyclic charge-discharge testing using this method, and the capacity retention of the lithium-ion batteries after 800 cycles was calculated.
[0181] 2) High temperature storage stability
[0182] At 25°C, the secondary batteries prepared in the examples and comparative examples were charged at a constant current rate of 0.5C to a charge cut-off voltage of 4.25V, then charged at a constant voltage to a current of ≤0.05C, allowed to stand for 5 minutes, and then discharged at a constant current rate of 0.33C to a discharge cut-off voltage of 2V, allowed to stand for 5 minutes. This constituted one charge and discharge cycle.
[0183] Then charge at a constant current rate of 0.5C to a charge cut-off voltage of 4.25V, and then charge at a constant voltage to a current ≤ 0.05C. After storing the battery at 60°C for 100 days, perform a cyclic charge and discharge test on the battery according to the above method to calculate the capacity retention rate of the lithium-ion battery after 100 days of storage.
[0184] 3. Analysis of test results of various embodiments and comparative examples
[0185] Secondary batteries of various embodiments and comparative examples were prepared according to the above methods, and various parameters were measured. The results are shown in Table 1 below.
[0186] Table 1
[0187] According to the results in Table 1, the negative electrode active material of the batteries of Examples 1-22 is a silicon-carbon composite material with a three-dimensional network cross-linked pore structure, and the electrolyte contains the first component. Compared with the battery in Comparative Example 1 in which the negative electrode active material is a silicon-carbon composite material with a three-dimensional network cross-linked pore structure and the electrolyte does not contain the first component, and the batteries in Comparative Examples 2-4 in which the negative electrode active material is a silicon-carbon composite material with a honeycomb pore structure and the electrolyte contains the first component, the batteries of Examples 1-22 exhibit higher cycle capacity retention and better storage capacity retention under high temperature conditions.
[0188] In the comparative example, the negative electrode is a silicon-carbon composite material with a honeycomb pore structure. Silicon particles are not easily deposited inside the honeycomb pore structure. Therefore, the mass content of silicon-based particles in the silicon-carbon composite material with a honeycomb pore structure is low, only 7%, and the silicon element is concentrated on the surface distribution of the composite material. The carbon matrix can hardly play a role in limiting the expansion of silicon-based particles, and the battery's cycle performance is poor.
[0189] From the comparison of Examples 12-13 with Examples 11 and 14, it can be seen that controlling the ratio EL:SSA between the specific surface area SSA of the silicon-carbon composite material and the mass proportion EL of the first component in the electrolyte in the range of 0.0004 to 0.01 can further improve the battery cycle capacity retention rate and the storage capacity retention rate of the battery under high temperature conditions.
[0190] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and within the scope of the technical solution of the present application, embodiments having substantially the same structure as the technical concept and exerting the same effects are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be conceived by those skilled in the art to the embodiments, and other methods constructed by combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery, characterized in that: include A negative electrode plate, the negative electrode plate comprising a silicon-carbon composite material having a three-dimensional network cross-linked pore structure; and An electrolyte solution comprises a first component, wherein the first component comprises a cyclic functional group containing a sulfate group or a sulfonate group.
2. The secondary battery according to claim 1, characterized in that: The first component comprises at least one of the compounds represented by Formula I, Formula II, and Formula III, Among them, L1-L6 each independently includes m is any integer from 0 to 8. When m is 0, L2 and L3 are connected by a single bond; R1, R2, and R3 are independently H, F, fluorine-substituted or unsubstituted C1-C 10 Saturated or unsaturated hydrocarbon group, C6~C 60 At least one of aryl, carbonyl, carboxyl, ester, cyano, silane and ether; M contains at least one of O and C; n is any integer from 0 to 3.
3. The secondary battery according to claim 1 or 2, characterized in that: The first component includes one or more of Compound A-1 to Compound A-10:
4. The secondary battery according to any one of claims 1 to 3, characterized in that: The specific surface area of the silicon-carbon composite material is SSA m 2 / g, Based on the total mass of the electrolyte, the mass proportion of the first component is EL g / g, EL: SSA is 0.001~0.03, and can be optionally 0.004~0.
01.
5. The secondary battery according to any one of claims 1 to 4, characterized in that: Based on the total mass of the electrolyte, the mass proportion of the first component is ELg / g, In the peripheral region of the silicon-carbon composite material, the mass percentage of silicon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material is B1, wherein the peripheral region of the silicon-carbon composite material is from the outer surface of the silicon-carbon composite material to the The area within the silicon-carbon composite material extending within a distance of r / 2, r represents the short diameter of the silicon-carbon composite material, EL: B1 is 0.001~0.1, and can be optionally 0.005~0.
06.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The total pore volume of the pores with a pore diameter greater than 100 nm in the silicon-carbon composite material is V1cm 3 / g, the ratio EL:V1 between the mass proportion EL of the first component in the electrolyte and the total pore volume V1 of the pores with a pore diameter greater than 100 nm in the silicon-carbon composite material is 1 to 30, and can be optionally 2 to 15.
7. The secondary battery according to claim 5 or 6, characterized in that: In the peripheral area of the silicon-carbon composite material, the mass percentage A1 of the carbon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material and the mass percentage B1 of the silicon element of the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material satisfy 0.8≤B1 / A1≤2.5, optionally, 1≤B1 / A1≤1.
5.
8. The secondary battery according to any one of claims 1 to 7, characterized in that: The mass percentage A of the carbon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material has a decreasing trend along the direction from the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material, and the mass percentage B of the silicon element in the silicon-carbon composite material relative to the total mass of the silicon-carbon composite material has an increasing trend along the direction from the geometric center of the silicon-carbon composite material to the outer surface of the silicon-carbon composite material.
9. The secondary battery according to any one of claims 1 to 8, characterized in that: The specific surface area SSA of the silicon-carbon composite material satisfies: 2m 2 / g≤SSA≤10m 2 / g; optionally, 3m 2 / g≤SSA≤7m 2 / g.
10. The secondary battery according to any one of claims 1 to 9, characterized in that: The silicon-carbon composite material comprises: carbon matrix particles, the carbon matrix particles comprising a three-dimensional network cross-linked pore structure; and silicon nanoparticles, at least a portion of which is disposed in the three-dimensional network cross-linked pore structure.
11. The secondary battery according to claim 10, characterized in that: The silicon nanoparticles include one or more of silicon oxide compounds, pre-lithium silicon oxide compounds, amorphous silicon, crystalline silicon and silicon-carbon composites, and may be amorphous silicon.
12. The secondary battery according to claim 10 or 11, characterized in that: The carbon matrix includes one or more of graphite, soft carbon and hard carbon.
13. The secondary battery according to any one of claims 10 to 12, characterized in that: The mass ratio of the silicon nanoparticles in the silicon-carbon composite material is greater than or equal to 40%, and can be optionally 40-60%.
14. The secondary battery according to any one of claims 1 to 13, characterized in that: The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20000N is P11g / cm 3 The compaction density of the silicon-carbon composite material after 20 times of powder compaction under a force of 20000N is P21g / cm 3 The ratio satisfies: 1.00<P21 / P11≤1.20, optionally, 1.02≤P21 / P11≤1.
10.
15. The secondary battery according to any one of claims 1 to 14, characterized in that: The powder compaction density of the silicon-carbon composite material after one powder compaction under a force of 20000N is P11g / cm 3 Satisfies: 1.10≤P11≤1.40, optionally, 1.12≤P11≤1.
35.
16. The secondary battery according to any one of claims 1 to 15, characterized in that: The secondary battery includes at least one of a lithium ion battery, a sodium ion battery, a magnesium ion battery, and a potassium ion battery.
17. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 16.